Level of Midwife Knowledge about Referral to Outcome of Pregnant Women at Muara Teweh Regional Hospital - Ika Misna Puspita; Sismeri Dona; Eirene Eunike Meidiana Gaghauna (MBUnivPress, 2024)
From the data of North Barito MPDN, it was found that the highest mortality rate of mothers and babies was in Muara Teweh Regional Hospital in 2023, with 6 maternal deaths and 17 infant deaths. This is due to the delay in the referral process for pregnant women and newborns with complications. Midwives' knowledge about referrals is essential to determine the right time to make referrals to help reduce mortality rates. This study aims to determine the relationship between the level of knowledge of midwives about referrals to the outcome of pregnant women at Muara Teweh Regional Hospital. This study used a descriptive correlative method with a cross-sectional approach. With a total sampling of 70 midwives who make emergency referrals of pregnant women. Data analysis using chi-square statistical test The results showed that midwives had good knowledge of 71.4% of referrals. The results of the chi-square statistical test obtained a significant p-value of 0.734 (>0.05) there is no relationship between knowledge and the outcome of pregnant women based on the type of delivery and a significant p-value of 0.092 (>0.05) there is no relationship between midwife knowledge based on newborn complications. There is no relationship between the level of knowledge of midwives about referral and the outcome of pregnant women at Muara Teweh Regional Hospital. Based on the results of the study, it is necessary to carry out further guidance on referral not only for midwives but also for pregnant women and mothers.